Standardised patientsimulated practice learning: A rich pedagogical environment for psychiatric nursing education - A Jacobs; I Venter (South African Medical Association, 2017)
Background. Nursing education needs to adapt to be relevant to student nurses’ learning needs. This study investigates the use of standardised patients (SPs) in a simulated patient interview as a learning strategy to bridge the theory-practice gap. Simulation helps students to develop skills such as communication, higher cognitive thinking, decision-making and problem-solving. There is evidence to support the use of SP case scenarios to enable students to develop their clinical and interpersonal skills in a controlled environment before encountering patients in a clinical setting.Objective. To explore and describe students’ experiences of the developed SP scenario for the mental health nursing interview.Methods. A qualitative approach was taken and data were gathered using structured open-ended questions to gather information from 33 undergraduate nursing students after they encountered the SP simulation. Participants’ responses were thematically analysed.Results. Nursing students experienced the simulation as challenging, but felt that being able to practise their skills within a safe simulated environment built confidence. They indicated that the experience was not only enjoyable, but that it helped them to integrate theory with practice, develop communication skills and feel professional.Conclusion. SP-simulated practice combined with classroom teaching is important in improving nurses’ professed ability to respond to patients’ needs. Nursing students need to be interpersonally competent before engaging with mental health users. SP-simulated learning helps student nurses to participate actively in a positive learning process; they then begin to understand the need for linking theory with practice.